Roles of the polymerase-associated protein genes in Newcastle disease virus virulence - Yu, Xiao-hui; Cheng, Jin-long; Xue, Jia; Jin, Ji-hui; Song, Yang; Zhao, Jing; Zhang, Guo-zhong (Frontiers in Microbiology, 2017)
The virulence of Newcastle disease virus varies greatly and is determined by multiple genetic factors. In this study, we systematically evaluated the roles of the polymerase-associated (NP, P and L) protein genes in genotype VII NDV virulence after confirming the envelope-associated (F and HN) proteins contributed greatly to NDV virulence. The results revealed that the polymerase-associated protein genes individually had certain effect on virulence, while transfer of these three genes in combination significantly affected the chimeric virus virulence, especially when the L gene was involved. These results indicated that the L protein was a major contributor to NDV virulence when combined with the homologous NP and P proteins. We also investigated viral RNA synthesis using NDV minigenome systems to assess the interaction between the NP, P, and L proteins, which showed that the activity of the polymerase-associated proteins were directly related to viral RNA transcription and replication.